Evaluating Private Lands for Conservation of Wildlife - Martin B. Main; Mark E. Hostetler; Annisa Karim (EDIS)
In this document, we present criteria for evaluating land in terms of conserving wildlife species. There are several basic principles of conservation planning that can assist private landowners and organizations in assessing the wildlife value of a property. We have listed seven broad criteria for consideration when evaluating and prioritizing areas for wildlife. This document is WEC 164, one of a series of the Department of Wildlife Ecology and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences (IFAS), University of Florida. First published: September 2003.